2008
DOI: 10.1523/jneurosci.2895-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Enhanced Logical Consistency during Decision Making in Autism

Abstract: The emotional responses elicited by the way options are framed often results in lack of logical consistency in human decision making. In this study, we investigated subjects with autism spectrum disorder (ASD) using a financial task in which the monetary prospects were presented as either loss or gain. We report both behavioral evidence that ASD subjects show a reduced susceptibility to the framing effect and psycho-physiological evidence that they fail to incorporate emotional context into the decision-making… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
183
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(221 citation statements)
references
References 20 publications
28
183
5
1
Order By: Relevance
“…It is therefore intriguing to speculate that a decrease in the suppressive field gain term in autism can result in reduced contextual sensitivity in value-based decisions. Consistent with this prediction, enhanced logical consistency in value-based decisions is observed in autism as a consequence of reduced susceptibility to contextual framing (76).…”
Section: Rationalitymentioning
confidence: 59%
“…It is therefore intriguing to speculate that a decrease in the suppressive field gain term in autism can result in reduced contextual sensitivity in value-based decisions. Consistent with this prediction, enhanced logical consistency in value-based decisions is observed in autism as a consequence of reduced susceptibility to contextual framing (76).…”
Section: Rationalitymentioning
confidence: 59%
“…Bipolar patients were more intuitive than unipolar depressed patients (Liebowitz et al, 1979;Janowsky et al, 1999). Autism patients were characterized by deficient intuition and lacked spontaneous adaptation (Allman et al, 2005;De Martino et al, 2008). A recent study has shown behavioral and psychophysiological evidence that autism patients were more rational and less likely to be guided by their intuition and emotional context in a financial task (De Martino et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Autism patients were characterized by deficient intuition and lacked spontaneous adaptation (Allman et al, 2005;De Martino et al, 2008). A recent study has shown behavioral and psychophysiological evidence that autism patients were more rational and less likely to be guided by their intuition and emotional context in a financial task (De Martino et al, 2008). Our findings of opposing oxytocin effects on social cognition draw caution to the oxytocin pharmacotherapy for social dysfunction in that whether the effects of oxytocin on social functioning or emotional processing are facilitative, debilitative, or null, depending on an individual's cognitive style (Bartz et al, 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of depressive realism is controversial (for recent evidence against the phenomenon, see Baker et al 2011), but similar phenomena have been observed for other diagnoses. There is evidence in autism and schizophrenia that the reasoning tendencies partially responsible for the formation of pathological beliefs, or underlying pathological behavior, can also have epistemic benefits relative to those found in the non-clinical population (Tateno 2013;De Martino et al 2008;Owen et al 2007). For instance, people with schizophrenia have been found to be less vulnerable to framing effects, and do not exhibit a statistically normal but procedurally irrational increased tendency to gamble when faced with a certain loss (Brown et al 2013).…”
Section: Is Epistemic Rationality the Mark Of Mental Illness?mentioning
confidence: 99%
“…This processing style confers many advantages, but also disadvantages, as seen in the difficulty that most people have remembering random lists of words; in visual illusions induced by contextual features; and in framing effects that are examples of epistemic irrationality that is widespread in the general population. On a range of these kinds of tasks there is increasing evidence that autistic people tend to outperform non-clinical controls (e.g., De Martino et al 2008; for overview Happe 1999, Mottron 2011.…”
Section: Neurodiversity and Mental Capacitymentioning
confidence: 99%